2003
DOI: 10.1063/1.1637720
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated emission in nanocrystalline silicon superlattices

Abstract: We studied the conditions under which optical gain is measured in nanocrystalline silicon (nc-Si) using the variable stripe length method. Waveguide samples have been produced by magnetron sputtering of alternating layers of Si and SiO2, followed by high temperature annealing. No optical gain was observed under continuous wave pumping conditions. Under high intensity pulsed excitation, a superlinear fast (10 ns) recombination component yielding an optical gain up to 50 cm−1 has been independently measured in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4
2

Relationship

3
7

Authors

Journals

citations
Cited by 152 publications
(75 citation statements)
references
References 15 publications
3
72
0
Order By: Relevance
“…Optical losses of 15-20 cm −1 have been reported in porous silicon grains embedded in sol-gel derived SiO 2 matrix, 24 while values of 30-40 cm −1 have been reported for Si-nc. 25,26 Lower values ͑about 2.6 cm −1 ͒ have been reported for thick slab waveguides at 780 nm by means of shiftexcitation-spot technique. 17 In the same paper, losses of about 0.9 cm −1 have been found for longer propagation wavelengths ͑1000 nm͒ where Rayleigh scattering is decreased according to the well-known 1 / 4 law.…”
Section: -6mentioning
confidence: 99%
“…Optical losses of 15-20 cm −1 have been reported in porous silicon grains embedded in sol-gel derived SiO 2 matrix, 24 while values of 30-40 cm −1 have been reported for Si-nc. 25,26 Lower values ͑about 2.6 cm −1 ͒ have been reported for thick slab waveguides at 780 nm by means of shiftexcitation-spot technique. 17 In the same paper, losses of about 0.9 cm −1 have been found for longer propagation wavelengths ͑1000 nm͒ where Rayleigh scattering is decreased according to the well-known 1 / 4 law.…”
Section: -6mentioning
confidence: 99%
“…The presence of these defects results in a photoluminescence band typically at higher emission energy than the band related to the exciton recombination and differs from the later one in decay time and temperature dependence (Tsybeskov et al, 1994;Kanemitsu 1994;Min et al, 1996;Kanemitsu et al 1997). The oxygen related surface states are also believed to play an important role in the observation of stimulated emission from Si-QDs , Ruan et al, 2003. Finally in a series of studies it is observed that the photoluminescence properties of silicon containing films depend also on film stress and on the stress at the interface between the Si-QD and the matrix (Khriachtchev et al, 2001;Daldosso et al, 2003;Zatryb et al, 2011).…”
Section: Optical Properiesmentioning
confidence: 99%
“…Silicon nanocrystals situated in a much wider band gap SiO 2 can effectively localize electrons with quantum confinement, which improves the radiative recombination probability, shifts the emission spectrum toward shorter wavelengths, and decreases the free carrier absorption. Optical gain and stimulated emission have been observed from these Si nanocrystals by both optical pumping [3,4] and electrical injection [5], but the origin of the observed optical gain has not been fully understood as the experiments were not always reproducible -results were sensitive to the methods by which the samples were prepared. In addition, before Si-nanocrystal based lasers can be demonstrated, the active medium has to be immersed in a tightly confined optical waveguide or cavity.…”
Section: Introductionmentioning
confidence: 99%